Vegetation Characteristics and Nutrient Composition of Underwood Flora in Sal, Eucalyptus and Brushwood Forest Watersheds of Doon Valley - Joshie, P.; Narain, Pratap (Indian Forester, 1994)
A study on underwood vegetation of Sal (Shorea robusta) Eucalyptus and Brushwood watersheds in Doon Valley revealed that Sal had more underwood species (31), followed by Eucalyptus (16) and Brushwood (14). Quotient of similarity values (Sorensen) of ground flora were 46.8% and 35.5% for coppiced Eucalyptus and Brushwood watersheds respectively as compared with 100% for Sal water-sheds while the Brushwood ground flora revealed 60% value in comparison to Eucalyptus 100%. Maximum density of ground flora was found in coppiced Eucalyptus (210000 ha-1) followed by Brushwood (105000 ha-1) than in Sal forest (83958 ha-1). The comparative basal cover followed the order: Coppiced Eucalyptus 17.42 > mixed brushwood 15.84 > Sal 7.87 cm2m-2. Though the diversity was maximum in the Sal underwood flora, the concentration of dominance was maximum in Coppiced Eucalyptus and minimum in Sal flora. Further the lowest diversity in Sal flora (1.32) indicated that Sal forest represented the optimum expression on these sites. The understorey biomass was 9957 kg ha-1 in Eucalyptus. 8977kg ha-1 in mixed brushwood and 3441 kg ha-1 in Sal forests. The total nutrients locked in the understorey vegetation were in the same order but the percentage of these nutrients was more in Sal underwood vegetation. Higher phosphorus content was observed in these species under Sal than in Eucalyptus and Brushwood watershed, which is explained by neutral soil environments under Sal forest.